Implementation of the Pancasila Student Profile Strengthening Project on Improving Students' Social Attitudes Using the Rasch Model at SMPN 1 Bekasi City - Mursyidi, Wathroh; Sholeha, Miratus; Sari, Eva Dwi Kumala (Al'Adzkiya Journal, 2024)
The degradation of social values among students is increasingly concerning; the Ministry of Education launched a new program from the Merdeka curriculum, namely the Pancasila student profile strengthening project, which needs to be implemented in every educational institution. The purpose of this study was to examine the impact of the Pancasila student profile strengthening project program on students' social attitudes at SMPN 1 Bekasi City. The population in this study was 262 students in grade VIII, the sample was taken based on the Isaac and Michael table totaling 149 students using simple random sampling technique. The research data were obtained through a student social attitude questionnaire, which amounted to 30 question items. The data analysis technique uses the Rasch model with the Winsteps application. Data analysis was carried out through validity, reliability, descriptive statistics, logit item values, and exposure separation of the level of social attitudes of students at SMPN 1 Bekasi City. The results showed that students' social attitudes were classified as moderate, namely 90%, with an average value of 1.04 - 2.84 logit. These results prove that students' social attitudes improve with project activities to strengthen the Pancasila student profile and a positive learning environment.